1998
DOI: 10.1016/s0896-6273(00)80497-3
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Cadherin Family of Cell Adhesion Molecules in Hippocampal Long-Term Potentiation

Abstract: The cadherins are a family of cell-cell adhesion molecules that mediate Ca2+-dependent homophilic interactions between cells and transduce signals by interacting with cytoplasmic proteins. In the hippocampus, immunostaining combined with confocal microscopy revealed that both neural- (N-) and epithelial- (E-) cadherin are present at synaptic sites, implying a role in synaptic function. Pretreatment of hippocampal slices with antibodies (Abs) raised against the extracellular domain of either N-cad or E-cad had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
229
2
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(248 citation statements)
references
References 51 publications
(39 reference statements)
16
229
2
1
Order By: Relevance
“…Evidence for the latter is provided by the observation that the disturbance of synaptic cell adhesion, e.g., in mutant animals or by the application of antibodies or competitive peptides, in many cases interferes with long-term changes of synaptic plasticity. This has been reported for Ig superfamily CAMs NCAM180 and L1 (15,16), telencephalin (17), Fasciclin 2 (18), and Aplysia apCAM (19), as well as for cadherins (20) and integrins (21,22).…”
supporting
confidence: 61%
“…Evidence for the latter is provided by the observation that the disturbance of synaptic cell adhesion, e.g., in mutant animals or by the application of antibodies or competitive peptides, in many cases interferes with long-term changes of synaptic plasticity. This has been reported for Ig superfamily CAMs NCAM180 and L1 (15,16), telencephalin (17), Fasciclin 2 (18), and Aplysia apCAM (19), as well as for cadherins (20) and integrins (21,22).…”
supporting
confidence: 61%
“…Several recent studies support a role for the classic cadherins in synaptic plasticity (Tang et al 1998;Benson & Tanaka 1998;Tanaka et al 2000;Bozdagi et al 2000). We previously reported (Tang et al 1998) that either cadherin function-blocking antibodies or inhibitory peptides blocked LTP in area CA1 of rat hippocampal slices.…”
Section: Introductionmentioning
confidence: 89%
“…Cadherins are a family of proteins that mediate Ca 2ϩ -dependent homophilic cell adhesion (Takeichi 1990). Cadherins are located at synaptic sites (Fannon & Colman 1996;Uchida et al 1996;Tang et al 1998) and biochemical studies have demonstrated that cadherins associate with core synaptic proteins both pre-and postsynaptically (Husi et al 2000;Phillips et al 2001), suggesting that cadherins regulate synaptic function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several reports have shown that N-cadherin and its cognate cytoplasmic interacting protein betacatenin regulate synaptic structure and functions in an activity-dependent manner (Murase et al, 2002;Togashi et al, 2002;Yu and Malenka, 2003). This is of a particular interest because N-cadherin has been shown to be modified by neuronal activity and to play important roles in synaptic plasticity (Tang et al, 1998;Bozdagi et al, 2000;Tanaka et al, 2000). N-cadherin associates and co-localizes with AMPARs in neurons, in a cis manner, and this association is regulated by the extracellular Ca 2ϩ concentration (Nuriya and Huganir, 2006).…”
Section: Ampar Regulation By Cell Adhesion Molecules (Cams)mentioning
confidence: 99%